2013
DOI: 10.1183/09059180.00003413
|View full text |Cite
|
Sign up to set email alerts
|

Sleep apnoea and metabolic dysfunction

Abstract: Obstructive sleep apnoea (OSA) is a highly prevalent condition often associated with central obesity. In the past few years, several studies have analysed the potential independent contribution of OSA to the pathogenesis of metabolic abnormalities, including type 2 diabetes, the metabolic syndrome and nonalcoholic fatty liver disease. New perspectives in OSA patient care have been opened by the promotion of lifestyle interventions, such as diet and exercise programmes that could improve both OSA and the metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
94
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(98 citation statements)
references
References 96 publications
0
94
1
3
Order By: Relevance
“…Obstructive sleep apnoea is a highly prevalent condition often associated with central obesity, which could contribute to worsen insulin resistance and lead to impaired glucose tolerance and T2DM 27 . Improvement of sleep apnoea with weight reduction can also improve insulin sensitivity and glucose profile.…”
Section: Comorbidities Shared and Magnified By Both Obesity And Diabetesmentioning
confidence: 99%
“…Obstructive sleep apnoea is a highly prevalent condition often associated with central obesity, which could contribute to worsen insulin resistance and lead to impaired glucose tolerance and T2DM 27 . Improvement of sleep apnoea with weight reduction can also improve insulin sensitivity and glucose profile.…”
Section: Comorbidities Shared and Magnified By Both Obesity And Diabetesmentioning
confidence: 99%
“…, Yoshifumi Saisho 1) , Koichi Fukunaga 2) , Mizuha Haraguchi 2) , Wakako Yamasawa 2) , Isao Kurihara 1) , Tomoko Betsuyaku 2) and Hiroshi Itoh 1) OBESITY is associated with both type 2 diabetes (T2DM) and obstructive sleep apnea (OSA) [1][2][3]. It has been reported that approximately 25-80% of patients with T2DM are complicated by OSA, while approximately 15-30% of patients with OSA are complicated by T2DM [1][2][3].…”
mentioning
confidence: 99%
“…It has been reported that approximately 25-80% of patients with T2DM are complicated by OSA, while approximately 15-30% of patients with OSA are complicated by T2DM [1][2][3]. OSA is a treatable chronic sleep disorder characterized by recurrent episodes of complete (apnea) ted hemoglobin (HbA1c) level in Japanese individuals with and without T2DM.…”
mentioning
confidence: 99%
“…The growing prevalence of obesity and the increasing population body mass index has created major public health challenges [11] . Obstructive sleep apnea has been independently linked with hypertension, atrial fibrillation, cardiac disease, worsening of diabetes, insulin resistance, peri-operative and postoperative complications and coronary artery disease (CAD), to name the few [12][13][14][15][16] .…”
Section: Obstructive Sleep Apneamentioning
confidence: 99%